The influence of residual operating profit on stock returns: Empirical evidence from B3 S/A - Silva, Mateus Barreto Vieira da; Carvalho Junior, César Valentim de Oliveira; Cunha, Camila Rodrigues de Araujo Goes da (Contextus - Revista Contemporânea de Economia e Gestão, 2025)
Background: Among the most relevant accounting indicators for understanding corporate characteristics and supporting decision-making, metrics focused on operational activities stand out. These indicators may offer greater efficiency in predicting stock returns, as they encompass a business's core transactions and provide a more accurate representation of a firm's financial condition. Purpose: This study investigates the explanatory power of residual operating income—measured by the Return on Net Operating Assets (RNOA) and the Weighted Average Cost of Capital (WACC)—on stock returns. It hypothesizes the existence of a significant relationship between stock returns and residual operating income. Method: Data were collected from companies listed on B3 — excluding financial institutions, holding companies, real estate funds, and investment vehicles—via the Refinitiv Eikon© system from 2015 to 2022. The final sample comprised 1,224 observations. Statistical tools employed include descriptive analysis, correlation matrix, quantile regression, and time series analysis. Results: The findings indicate that residual operating income explains stock returns in the 0.25 and 0.75 quantiles, suggesting the proposed metric's predictive power. The impact of the COVID-19 pandemic proved significant across all quantiles, highlighting its relevance to financial markets. Time series analysis revealed that stock returns closely tracked residual operating income throughout the study period, except in 2017 and 2022. Conclusions: This study contributes to the accounting literature by introducing a novel metric for the Brazilian context and offers practical implications for financial markets. This metric supports more informed decisions by investors, financial analysts, and managers